Pelatihan Media Pembelajaran Interaktif Menggunakan Website Quizizz Untuk Guru Smp Pelita Medan - Nurianti Sitorus; Raju Gobal; Andrian; Ika Agustina; Reniwati Lubis (Jurnal Pengabdian Masyarakat, 2023)
The development of computer technology has changed the way humans carry out activities. In the world of education, a teacher no longer has to focus on books as a learning medium. In this modern era, students called generation Z are already technologically literate, so learning methods that use technology are needed that can attract students' attention. Many interesting applications have been developed to support learning activities. There are Android-based and website-based ones. Each application has its own advantages and disadvantages. Quizizz is a website that is widely used as a learning medium because Quizizz is an interactive learning media. With interactive learning media training using the quizizz website, teachers are more creative in stimulating students' interest in learning and can improve student achievement..